Characteristics and deterioration mechanisms in coral stones used in a historical monument in a saline environment. (30th April 2020) - Manohar, Swathy; Bala, Karpagam; Santhanam, Manu; Menon, Arun
Highlights: Weathering assessment of coral stone masonry from a heritage structure. Use of microanalytical techniques to reveal the characteristics of coral stone. Microstructure and morphology are linked to the durability performance. Good salt weathering resistance of coral stones, proved from accelerated weathering studies. Abstract: Information on properties and behavior of the ancient materials is critical in adopting appropriate strategies for preservation of historic monuments. Coral stones are materials with unique physical properties, and is common in ancient stone constructions. But these are not commonly in use in new buildings, and even quarrying of coral stones is banned in several island countries. However, considering the importance in heritage protection, there is a need to define their properties and performance. The current paper documents the condition and typical damage patterns of a coral stone heritage structure and analyses the physical, mechanical and chemical properties of the coral stone through in-situ and lab tests. The material properties and the microstructural details are examined to understand weathering of coral stone. The resistance of the material to salt crystallization was studied by performing sodium sulfate and sodium chloride immersion and drying cycles. Based on the results of the microstructural modifications seen on artificial salt weathering, the unique pore distribution system in the coral stones is found as the key for a higher resistance to crystallization of soluble salts. Erosion due to rain water and wind are concluded as the potential causes for the kind of damages observed.